Analysis of the Role of Professional Organizations in Career Development, Professional Ethics, Challenges, and Career Development Strategies Among Educators at Smpn 4 Mataram - Jaufil Laili; Isma Nova Liana; Dhea Kapril Amanda; Selviana Purwaningsih; Edy Herianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study analyzes the role of professional organizations, particularly the Subject Teacher Association (MGMP), in supporting career development and professional ethics among teachers at SMPN 4 Mataram. Faced with professional and educational demands, organizations like MGMP are vital for helping teachers improve their competencies through training, mentorship, and collaborative efforts. The findings indicate that MGMP plays a strategic role in enhancing teaching skills, reinforcing professional ethics, and providing solutions to instructional challenges. However, MGMP also faces challenges, such as limited resources and varied member participation. As part of development strategy, strengthening managerial support and increasing synergy between the school and MGMP are essential steps to maximize MGMP’s impact in supporting educators.